2005
DOI: 10.1002/ejlt.200401077
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature esterification of fatty acids with methanol at ambient pressure

Abstract: High-temperature esterification of fatty acids with methanol at ambient pressureThe article presents the results of the kinetic study of the acid-catalyzed esterification of free fatty acids (FFA) with methanol (MeOH) at elevated temperatures above the boiling point of MeOH, at ambient pressure, and at continual flow of liquid MeOH into the reaction mixture. Under these conditions, the reaction follows the rate equation valid for reactions of the first order. Beside temperature, the pseudo rate constant depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The OL contains usually about 30-50 wt-% of FAME. Its technical application can be envisaged mainly in two directions: either for decomposing the present FAME to FFA and thus converting the OL to technical fatty acids or, alternatively, for esterifying the FFA by methanol to FAME and using the formed FAME as, e.g., an alternative diesel fuel (Kocsisová et al [10]). There is also a series of fatty acid applications in which it is not important whether an acyl is in the form of a free acid or of a methyl ester.…”
Section: Hydrolysis Of Estersmentioning
confidence: 99%
“…The OL contains usually about 30-50 wt-% of FAME. Its technical application can be envisaged mainly in two directions: either for decomposing the present FAME to FFA and thus converting the OL to technical fatty acids or, alternatively, for esterifying the FFA by methanol to FAME and using the formed FAME as, e.g., an alternative diesel fuel (Kocsisová et al [10]). There is also a series of fatty acid applications in which it is not important whether an acyl is in the form of a free acid or of a methyl ester.…”
Section: Hydrolysis Of Estersmentioning
confidence: 99%
“…The use of a heterogeneous catalyst has the following inherent advantages over catalysis effected by dissolved electrolytes: (a) they eliminate the corrosive environment; (b) the catalyst can be easily recycled from the reaction mixture by decantation or filtration; (c) the purity of the products is higher since the side reactions can be completely eliminated or are less significant. There are very few reports on the esterification kinetics of fatty acids for a homogeneous catalyst system [3,4] and a heterogeneous catalyst system [5][6][7][8][9]. Kinetic models and results were reported for the reaction of fatty acids and various types of alcohols with short chain such as methanol in the production of biodiesel fuel [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There are very few reports on the esterification kinetics of fatty acids for a homogeneous catalyst system [3,4] and a heterogeneous catalyst system [5][6][7][8][9]. Kinetic models and results were reported for the reaction of fatty acids and various types of alcohols with short chain such as methanol in the production of biodiesel fuel [5,6]. When the reaction of oleic acid or fatty acid mixtures with methanol was investigated in the presence of H 2 SO 4 and p-toluene sulfonic acid, it was found that p-TSA is more effective [10].…”
Section: Introductionmentioning
confidence: 99%
“…As heterogeneous catalyst also cationic ion exchange resins can be used in continuous reaction columns; however, this approach has only been used so far in pilot plants. The esterification of free fatty acids with methanol at increased temperatures above the boiling point of methanol at ambient pressure was achieved by introducing methanol into a preheated reaction mixture, 15 containing free fatty acids and an acid catalyst. The reaction rates were significantly higher than under reflux temperature.…”
Section: Acid Catalysismentioning
confidence: 99%